Evaluation of Family Effects in the Context of Power, Experience and Culture on Business and Management in the Family Firms - Top, Seyfi; Atan, Özlem; Öge, Ercan; Dilek, Serkan (Elsevier BV, 2013)
AbstractThe aim of this study is to examine the relationship among the power factors that located on the family effectiveness. Power is the ability to influence and leading people and business to achieve goals. The effectiveness of family in the family firms evaluated the relationships under the three major sub-title as properties of ownership (capital), experience, and culture. One of the family power is ownership. Ownership covers capital, the board of directors and family leadership, and vision. Another measure of the effects on the family firm is experience. Experience sub-scale also is represented in the two sub-scales such as generations of the governing and participation the general assembly and management in the life cycle of the firm. Another parameter that measures the impact on the family on the firm is culture. Culture in sub-scale will be discussed as family overlapping values, authority and respect between generations compliance with inter-generational commitment or cognitive. We can evaluate that as increase amount of family capital, impress family's representation on board of directors and firm control. As impress family's representation on board of directors and family control of the firm increase family leadership and vision positively. As family's vision gets better and its leadership role systematically gets stable, family effectiveness on firm increases. As family's leadership position improves the family's features of cohesiveness and devotion improves family power over the firm. As increase family's power of leadership and vision increase the use of family's effectiveness on the firm.
Keywords: Experience; Family Effect; Power; Culture; 8. Economic growth